2021
DOI: 10.3390/textiles1020008
|View full text |Cite
|
Sign up to set email alerts
|

Development of Piezoresistive Sensor Yarn to Monitor Local Fabric Elongation

Abstract: The performance of bulletproof vests is mainly based on the energy absorption capacity of the flexible fibrous reinforcements. To understand the in situ behaviour of these textile structures during a ballistic impact, we find the use of sensor yarns integrated into these fibrous reinforcements to be a non-invasive and reliable solution. Measurements of the dynamic deformation of the sensor yarns will provide a new and useful source of information. The design and manufacturing stages of a sensor yarn, made with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Further examining thin films with 5 AgNW deposition cycles, as shown in Figure S3c, revealed that the dense AgNW network preserved the connectivity, even across cracks, suggesting that resistance changes were negligible despite repeated stretching. Our experimental results that the resistance of strain-sensors change nonlinearly are consistent with a general nanowire percolation network model, which follows the equation:: R / R 0 = (1 + ε) t . , Here, t is an exponent that characterizes the sensitivity of the resistance to the applied strain, dependent on the material properties and the geometry of the structure (related to the number of contact points and the density of deposited AgNWs). Electrical pathway connections are made where the AgNWs touch each other, and these contact points can remain connected even when deformed by stretching: As stretching increases, the number of contact points may decrease or the quality of these contacts may deteriorate, leading to increased resistance.…”
Section: Resultssupporting
confidence: 81%
“…Further examining thin films with 5 AgNW deposition cycles, as shown in Figure S3c, revealed that the dense AgNW network preserved the connectivity, even across cracks, suggesting that resistance changes were negligible despite repeated stretching. Our experimental results that the resistance of strain-sensors change nonlinearly are consistent with a general nanowire percolation network model, which follows the equation:: R / R 0 = (1 + ε) t . , Here, t is an exponent that characterizes the sensitivity of the resistance to the applied strain, dependent on the material properties and the geometry of the structure (related to the number of contact points and the density of deposited AgNWs). Electrical pathway connections are made where the AgNWs touch each other, and these contact points can remain connected even when deformed by stretching: As stretching increases, the number of contact points may decrease or the quality of these contacts may deteriorate, leading to increased resistance.…”
Section: Resultssupporting
confidence: 81%